Practical data migration - Morris, Johny (UK : BCS Learning and Development Ltd., 2012)
This book is for executives and practitioners tasked with the movement of data from old systems to a new repository. It uses a series of steps guaranteed to get the reader from an empty new system to one that is working and backed by the user population. Using this proven methodology will vastly increase the chances of a successful migration.
Includes index.
Keywords: Database management; Electronic data processing